(untitled) (Revista Justiça do Direito, 2025)
The article examines the concept of the standard of proof in common and continental law, and considers approaches to determining the level of evidentiary force required for a court decision. The author analyzes the development of the doctrine of proof in the Anglo-American and European legal systems, compares the criteria used in civil, criminal and administrative proceedings. Particular attention is paid to such categories as beyond reasonable doubt and preponderance of evidence, which are key to Anglo-Saxon law, as well as the role of judicial discretion and formalized rules of evidence in the continental system. The author identifies the main problems of standardization of evidence, including issues of legal certainty, objectivity and admissibility of evidence. The analysis suggests possible ways to harmonize approaches to the evaluation of evidence in the international context. Special attention is paid to the interaction between the general and continental approaches to the process of evidence, given the growing integration of legal systems and the development of international cooperation in the field of justice. The author analyzes the practice of international judicial bodies, such as the European Court of Human Rights and the International Criminal Court, which play a key role in the development of universal standards for the evaluation of evidence.